Towards a comprehensive measurement of the information rich and poor: Based on the conceptualization of individuals as information agents. Issue 4 (11th July 2016) - Yu, Liangzhi; Zhou, Wenjie; Yu, Binbin; Liu, Hefa
Abstract : Purpose: – Following the assumption that studies of information inequality need to be based on precise discrimination between society's information rich and poor and against the context that a mechanism for such discrimination is still lacking, the purpose of this paper is to explore the possibility of establishing a holistic informational measurement. Design/methodology/approach: – It does so by developing a measurement based on the conceptualization of the individual as an information agent and his/her information world as his/her characterization. The development procedure consists of four steps: operationalization of the theoretical constructs and the initial drafting of the questionnaire instrument; revisions of the questionnaire based on pilot tests with small groups of people; weighing of the questionnaire items for the purpose of calculating index-type variable scores; formal test of validity and reliability. Findings: – The resulting measurement consists of eight variables corresponding to eight theoretical constructs of an individual's information world, each being measured by a group of questionnaire-based items which, in turn, generate an index-type score as the variable's value. Validity and reliability tests show that the measurement is, on the whole, able to distinguish the information poor from the information rich and to measure individuals consistently. Originality/value: – The study demonstrates that it is possible to distinguish the information rich and poor by informational measurement in the same way as to distinguish economic groups by income, ethnic groups by race and intelligence groups by IQ; and that such a measurement has arguably multifaceted value for information inequality research.